Prospects For Improving The Efficiency Of Human Resources In Uzbekistan (Diversity Research: Journal of Analysis and Trends, 2024)
Prospects for improving the efficiency of human capital in Uzbekistan are economic development of entrepreneurship and social modernization of education, bringing society to a high example of welfare and human value.